New Approach in E-mail Based Text Steganography - Tutuncu, Kemal; Hassan, Abdikarim Abi (International Journal of Intelligent Systems and Applications in Engineering, 2015)
In this study combination of lossless compression techniques and Vigenere cipher was used in text steganography that makes use of email addresses to be the keys to reconstruct the secret message which has been embedded into the email text. After selecting the cover text that has highest repetition pattern regarding to the secret message the distance matrix was formed. The members of distance matrix were compressed by following lossless compression algorithms as in written sequence; Run Length Encoding (RLE) + Burrows Wheeler Transform (BWT) + Move to Forward (MTF) + Run Length Encoding + Arithmetic Encoding (AE). Â Later on Â Latin Square was used to form stego key 1and then Vigenere table was used to increase complexity of extracting stego key 1. Final step was to choose e-mail addresses by using stego key 1 and stego key 2to embed secret message into forward e-mail platform. The experimental results showed that proposed method has reasonable performance with high complexity.